Analisis Penerapan Manajemen Kas Dalam Pengelolaan Keuangan UMKM Konter Pulsa Fahmi Cell - Dhelzahra Yashinta; Sungkono (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This study analyzes the implementation of cash management at the Fahmi Cell UMKM (Micro, Small, and Medium Enterprises) Pulse Counter located in East Karawang. The objective of this research is to identify the cash management practices applied and assess their effectiveness in maintaining liquidity and financial stability. The research method used is descriptive quantitative, with data collected from financial statements, cash transaction records, and other related documents. The results show that Fahmi Cell implements strict cash management policies, including credit policies, efficient cash operational procedures, and accurate cash forecasting and budgeting. Deviation analysis and routine monitoring are also conducted to ensure optimal cash management. The discussion reveals that effective cash management can reduce financial risks and support business growth. The conclusion of this study is that good cash management is crucial for UMKM to maintain their financial health. It is recommended that UMKM continuously improve financial literacy through ongoing training and utilize technology for cash flow recording and monitoring. Additionally, access to financial resources such as low-interest loans is essential to support capital needs.